2018
DOI: 10.1111/adb.12603
|View full text |Cite
|
Sign up to set email alerts
|

Activation of amylin receptors attenuates alcohol‐mediated behaviours in rodents

Abstract: Alcohol expresses its reinforcing properties by activating areas of the mesolimbic dopamine system, which consists of dopaminergic neurons projecting from the ventral tegmental area to the nucleus accumbens. The findings that reward induced by food and addictive drugs involve common mechanisms raise the possibility that gut-brain hormones, which control appetite, such as amylin, could be involved in reward regulation. Amylin decreases food intake, and despite its implication in the regulation of natural reward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 96 publications
2
34
1
Order By: Relevance
“…In contrast to an attenuation of alcohol-induced locomotor stimulation as previously observed (Kalafateli et al 2019b), we here notice that the alcohol response is greater in sCTtreated mice compared with that in vehicle-treated mice. However, co-administration of sCT and alcohol for 5 days did not alter any secondary behavioural parameters as measured in this locomotor activity experiments.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to an attenuation of alcohol-induced locomotor stimulation as previously observed (Kalafateli et al 2019b), we here notice that the alcohol response is greater in sCTtreated mice compared with that in vehicle-treated mice. However, co-administration of sCT and alcohol for 5 days did not alter any secondary behavioural parameters as measured in this locomotor activity experiments.…”
Section: Discussioncontrasting
confidence: 99%
“…The agonist was administered 30 min prior to alcohol administration in the experimental setup, where alcohol was administered the same day with sCT. This dose of sCT was used, as we have previously established that this dose attenuates alcohol-mediated behaviours in rodents (Kalafateli et al 2019a ; Kalafateli et al 2019b ). Moreover, this sCT dose, at least acutely, does not affect blood alcohol concentration (Kalafateli et al 2019b ), rendering the possibility of pharmacokinetic interaction between the two drugs less likely.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the mechanism facilitating the improved food preference is unknown, we speculate that KBP-088 acts centrally as amylin agonism is known to affect dopamine release in the hypothalamus (Brunetti et al, 2002), which affects the feeding patterns (Szczypka et al, 1999(Szczypka et al, , 2000. This is supported by the observation that the DACRA, salmon calcitonin (sCT), reduces fat intake and to some extent sucrose intake possibly via the ventral tegmental area and/or the area postrema (Mietlicki-Baase et al, 2017;Whiting et al, 2017), and have been suggested to be involved in blocking the reward mechanism normally induced by alcohol (Kalafateli et al, 2018). Hence, it is likely that KBP-088 influences food preference via central mechanisms.…”
Section: Discussionmentioning
confidence: 98%